1986
DOI: 10.1584/jpestics.11.253
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Pyrethroid Insecticide Cypermethrin in Cabbages

Abstract: Metabolism in cabbage plants of (1R)-cis-and (1R)-traps-isomers of Cypermethrin [(RS)-a-cyano-3-phenoxybenzyl(1RS)-cis, trans-3-(2, 2-dichlorovinyl)-2, 2-dimethylcyclopropanecarboxylate] was investigated with 14C preparations labeled separately in the benzylphenyl ring and cyclopropyl ring. The half-life of disappearance was about 4-5 days and 7-8 days for traps-and cis-cypermethrin, respectively. Both isomers of cypermethrin underwent epimerization to (1 S)-isomers, cis/trans isomerization, ester bond cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Therefore, metabolic pathways of 1 seemed to be partly common among plants, mammals, fishes, and insects. As for the hydroxylation at the phenyl ring, a similar reaction has been reported for fenoxycarb (20) and some pyrethroids (19,(21)(22)(23)(24)(25)(26). These common profiles are supposed to be related to oxidases in plants.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, metabolic pathways of 1 seemed to be partly common among plants, mammals, fishes, and insects. As for the hydroxylation at the phenyl ring, a similar reaction has been reported for fenoxycarb (20) and some pyrethroids (19,(21)(22)(23)(24)(25)(26). These common profiles are supposed to be related to oxidases in plants.…”
Section: Discussionsupporting
confidence: 64%
“…The dissipation of cypermethrin has been studied on cotton leaves (Ware et al, 1983), wheat leaves (Westcott and Reichle, 1987), celery and lettuce (Braun et al, 1987), and cabbages (Furuzawa et al, 1981). The halflife for total cypermethrin in crop plants was several days.…”
Section: Introductionmentioning
confidence: 99%
“…The halflife for total cypermethrin in crop plants was several days. Furuzawa et al (1981) reported different halflives for cis-and trans-cypermethrin isomers in cabbage. The initial degradation half-lives of trans-and ciscypermethrin on and in treated cabbage leaves were 4-5 and 7-8 days, respectively, indicating that the trans-isomers degraded approximately twice as quickly as the cis-isomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,[117][118][119] Pyrethroids are generally susceptible to enzymatic hydrolysis and oxidation to form many metabolites in plant tissues, and the stereoisomers formed were mainly detected in a fraction of the plant surface rinse. Therefore, the observed isomerization in the cyclopropyl moiety is most likely to proceed photochemically under sunlight exposure, while no enantiomerization at 2-position of the acid moiety in fluvalinate (22) was observed.…”
Section: Plant Metabolismmentioning
confidence: 99%